Performance of Microalgae Chlorella sp. to Remove Phosphate in Domestic Wastewater Using Oxidation Ditch Algae Reactor (ODAR) - Jihan Ilvi Nurdiana; Ana Mauidatul Khasanah; Euis Nurul Hidayah; Naniek Ratni Juliardi A.R (Nusantara Science and Technology Proceedings)
Domestic wastewater contains high organic and inorganic materials. One alternative treatment that can be used is to use Oxidation Ditch Algae Reactor with microalgae Chlorella sp. The reactor is expected to reduce the concentration of phosphate in domestic wastewater. This study aims to determine the effectiveness and role of microalgae Chlorella sp in degrading phosphate in domestic wastewater. The variations used in this study were variations in the ratio of the volume of waste to microalgae (1: 0 and 1:2) and variations in conditions (oxic and oxic-anoxic). This research was conducted for five days each time running. The optimum yield of phosphate removal occurred under oxic-anoxic conditions with a volume ratio variation of 1:2, which was 78.81%. This study indicates that the microalgae Chlorella sp is effective for removing phosphate in domestic wastewater.